FACTORS INFLUENCING THE SCHOOL OPERATIONAL ASSISTANCE FUND (BOS) FUNDING STRATEGY IN OVERCOMING DISTORTIONS IN SCHOOL FINANCING COMMUNICATIONS - Prihatin, Selamet; Yuniar, Yuniar; Mardeli, Mardeli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the Principal's Strategy in the Implementation ofSchoolOperationalAssistanceFunding(Bos)FundinginOvercomingFundingCommunicationDistortionsinStateSeniorHighSchool3Prabumulih, South Sumatra Province. This research is a qualitative research.In data collection, researchers used several collection techniques, namely: (1)in-depth interviews, (2) observation, (3) documentation study. The dataanalysis technique uses the analytical method using the Miles and HubermanModel which consists of three stages, namely: data reduction, data display,and drawing conclusions or verification. Based on the results of research inthis study In order for the implementation of School Operational AssistanceFund(BOS)financinginovercomingdistortionsinfinancingcommunication, several aspects need to be carried out, including; Aspects offlexibility in the use of BOS Funds, Aspects of effectiveness in the use of BOSFunds, Aspects of efficiency in the use of BOS Funds, Aspects of accountabilityfor the use of BOS Funds and Aspects of transparency of BOS Funds